Effect of Phlogodym on Tourniquet Shock - Lázár, G; Karády, S; Husztik, E (Thrombosis and Haemostasis, 1969)
Our experiments revealed that Phlogodym had a marked adverse effect on the sublethal tourniquet shock of rats. This effect was associated with a simultaneous drop in fibrinogen levels and platelet counts. In the hind limbs of the animals treated with Phlogodym and submitted to tourniquet, a thrombo-hemorrhagic phenomenon which macroscopically and microscopically resembled the Shwartzman Reaction, developed 5 to 20 hrs after the removal of the tourniquet.